La responsabilité sociale de l’enseignement supérieur au Brésil - Monica Mota Tassigny; Emmanuelle Annoot (Éducation et Socialisation)
In a globalized world, the social responsibility of universities tends to go beyond their own frontiers. In an interview given to E. Annoot, Monica M. Tassigny, Professor in the university of Fortaleza UNIFOR, Brazil, explains the various possible links between universities and their communities. She outlines the role of social responsibility of Brazilian universities and more especially that of the university of Fortaleza.